2009
DOI: 10.1007/s00453-009-9294-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Expected Number of Bit Comparisons Required by Quickselect

Abstract: When algorithms for sorting and searching are applied to keys that are represented as bit strings, we can quantify the performance of the algorithms not only in terms of the number of key comparisons required by the algorithms but also in terms of the number of bit comparisons. Some of the standard sorting and searching algorithms have been analyzed with respect to key comparisons but not with respect to bit comparisons. In this paper, we investigate the expected number of bit comparisons required by Quicksele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Thus, in these cases the expected number of bit comparisons is asymptotically larger than that of key comparisons required to complete the same task only by a constant factor, since the expectation for key comparisons is asymptotically 2n. Fill and Nakama [8] also found that the expected number of bit comparisons required by QuickRand is also asymptotically linear in n (with slope approximately 8.207 31), as for key comparisons (with slope 3).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Thus, in these cases the expected number of bit comparisons is asymptotically larger than that of key comparisons required to complete the same task only by a constant factor, since the expectation for key comparisons is asymptotically 2n. Fill and Nakama [8] also found that the expected number of bit comparisons required by QuickRand is also asymptotically linear in n (with slope approximately 8.207 31), as for key comparisons (with slope 3).…”
Section: Introductionmentioning
confidence: 91%
“…Many studies have examined this algorithm to quantify its execution costs-a nonexhaustive list of references is [5], [8]- [10], [12]- [16], [18], [23]; all of them except for Fill and Nakama [8] and Vallée et al [23] have conducted the quantification with regard to the number of key comparisons required by the algorithm to achieve its task. As a result, most of the theoretical results on the complexity of QuickSelect are about expectations or distributions for the number of required key comparisons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…So, it is not straightforward to compare Quick Sort to a radix-based algorithm such as Radix Sort without considering the number of bit comparisons in both. We refer the reader to the recent work of Fill and Janson (2004), Fill and Nakama (2008), and Vallée et al (2009). This renewed interest in the analysis of algorithms from a bits point of view provided the motivation for us to consider radix selection, and to perform an analysis of the number of swaps, to further put in perspective a meaningful distinction between radix-based methods and comparison-based methods.…”
Section: Radix Methodsmentioning
confidence: 99%